2001
DOI: 10.1054/bjoc.2000.1711
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of total choline from in-vivo volume localized proton MR spectroscopy and its response to neoadjuvant chemotherapy in locally advanced breast cancer

Abstract: Breast cancer is the commonest cancer among women the world over. In India, the reported age adjusted incidence of breast cancer in women is about 26.7/1 00 000 population (NCRP, 1992). Unlike the West, in India, majority of the patients (about 60%) present with locally advanced breast cancer (LABC) or disseminated disease (Goel et al, 1995). In LABC, the treatment policy followed at most centres, is neoadjuvant chemotherapy (NACT) followed by surgery and local or locoregional radiotherapy. The response to NAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
238
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(250 citation statements)
references
References 27 publications
11
238
1
Order By: Relevance
“…Such studies have recently been carried out in breast cancer (Jagannathan et al, 2001;Meisamy et al, 2004), lymphoma and germ cell tumours (Schwarz et al, 2002), and glioma (Preul et al, 2000), where positive treatment response has been associated with reduction in the levels of total choline. Similar studies using phosphorous spectroscopy to detect changes in phosphocholine or phosphomonoesters have also been carried out in lymphoma (Arias-Mendoza et al, 2004) and head and neck cancer (Shukla-Dave et al, 2002a, b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies have recently been carried out in breast cancer (Jagannathan et al, 2001;Meisamy et al, 2004), lymphoma and germ cell tumours (Schwarz et al, 2002), and glioma (Preul et al, 2000), where positive treatment response has been associated with reduction in the levels of total choline. Similar studies using phosphorous spectroscopy to detect changes in phosphocholine or phosphomonoesters have also been carried out in lymphoma (Arias-Mendoza et al, 2004) and head and neck cancer (Shukla-Dave et al, 2002a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Proton magnetic resonance spectroscopy (MRS) can be used to characterise breast lesions through differences in the ratio of fat and water signals (Chu et al, 1987;Sijens et al, 1988) or the intensity of signal from choline-containing compounds (Bradamante et al, 1988;Katz-Brull et al, 2002;Bolan et al, 2003;Jacobs et al, 2004;Jacobs et al, 2005). Both fat : water ratios (Jagannathan et al, 1998) and choline levels (Preul et al, 2000;Jagannathan et al, 2001;Schwarz et al, 2002;Meisamy et al, 2004) have also been used to monitor treatment-induced changes, and phosphorous MRS has been used to predict response using differences in the levels of phosphocholine or phosphomonoesters (Shukla-Dave et al, 2002a, b;Arias-Mendoza et al, 2004). Sodium MRI might also be useful in monitoring treatment response (Kline et al, 2000;Schepkin et al, 2005).…”
mentioning
confidence: 99%
“…Elevated levels of choline-containing compounds (TCho) in water-suppressed spectra from neoplastic breast tissues have also been documented (23)(24)(25)(26). Changes in the levels of TCho can be used as a marker to assess the response of breast cancer patients to NACT (23).…”
mentioning
confidence: 99%
“…Elevated levels of choline-containing compounds (TCho) in water-suppressed spectra from neoplastic breast tissues have also been documented (23)(24)(25)(26). Changes in the levels of TCho can be used as a marker to assess the response of breast cancer patients to NACT (23). A recent study conducted at 4 T with an improved water-and fat-suppression sequence showed that TCho resonance could be observed in all patients with invasive carcinoma and in some patients with benign breast lesions (27).…”
mentioning
confidence: 99%
“…Analysis of early pooled clinical experience with in vivo 1 H MRS yielded a sensitivity and specificity for detection of breast cancer of 83% and 85%, respectively, with near 100% for both in a subgroup of young women [32]. A reduction or disappearance of the Cho signal has been associated with response to neoadjuvant chemotherapy of locally advanced breast cancer [33].…”
Section: Introductionmentioning
confidence: 99%